Fluorescent probe for determining hydrotalcite colloid sol crystallinity based on pi-pi stacking regulation and control fluorescence and preparation method of fluorescent probe
By using an imidazole-anchored naphthalene diamine (IANA) fluorescent probe based on π-π stacking regulation, the crystallinity of hydrotalcite colloid sol was solved, and the problem of large errors in determining the crystallinity of colloid sol in the prior art was solved, and a fast and accurate crystallinity determination was achieved.
Patent Information
- Application Number
- CN202411773259.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-12-04
AI Technical Summary
The existing technology is difficult to accurately determine the crystallinity of colloidal sol of nanomaterials, especially during the transition from liquid phase to solid powder, and common analytical techniques are affected by overlap between the crystalline and non-crystalline regions and the overlap of specific bands, resulting in high analytical errors.
The fluorescence probe based on π-π stacking regulation was used to bind naphthalene diamine (IANA) fluorophores to transition divalent metal ions through imidazole to adjust the degree of fluorescence quenching to determine the crystallinity of hydrotalcite colloid sol.
The rapid and accurate determination of the crystallinity of hydrotalcite colloid sol is achieved, and the analysis error is reduced, providing a new way to explore alternatives to X-ray diffraction.
Smart Images

Figure CN119613343A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of fluorescent probes, and particularly relates to a fluorescent probe for measuring the crystallinity of hydrotalcite colloidal sol by regulating fluorescence based on π-π stacking, and a preparation method thereof. Background Art
[0002] Colloidal sols of nanomaterials have excellent electrical and / or optical properties and have been widely used in the fields of sensing, catalysis, adsorption, energy and medicine. In general, their performance depends largely on their intrinsic structure, such as crystallinity. Currently, analytical techniques such as X-ray diffraction (XRD), differential scanning calorimetry, Raman spectroscopy, Fourier transform infrared spectroscopy (FT-IR) and terahertz spectroscopy have been reported, which are usually affected by the overlap between crystalline and non-crystalline regions and the overlap of specific bands, resulting in high analytical errors. In addition, these techniques are usually applicable to powder samples. It is reported that the crystallinity of the material changes during the transition from liquid phase to solid powder. At the same time, for colloidal sol XRD detection, solvent absorption largely affects the accuracy. Therefore, it is very necessary to explore a simple and rapid method for determining the crystallinity of colloidal sols. Summary of the invention
[0003] The purpose of the present invention is to provide a fluorescent probe for measuring the crystallinity of hydrotalcite colloidal sol based on π-π stacking-regulated fluorescence and a preparation method thereof.
[0004] The structural formula of the fluorescent probe for measuring the crystallinity of hydrotalcite colloidal sol based on π-π stacking-regulated fluorescence is as follows: .
[0005] The preparation method of the fluorescent probe for measuring the crystallinity of hydrotalcite colloidal sol based on π-π stacking-regulated fluorescence is as follows: 2,3-diaminonaphthalene and imidazole-2-carboxaldehyde are dissolved in a methanol-ethanol mixed solvent with a volume ratio of 0.5-2, heated under reflux for reaction for 20-30 hours, then cooled to room temperature, filtered, washed with methanol, and dried at 60-80°C to obtain the fluorescent probe.
[0006] The method for measuring the crystallinity of hydrotalcite colloidal sol is: (1) A fluorescent probe solution for determining the crystallinity of hydrotalcite colloidal sol by fluorescence regulation based on π-π stacking is mixed with water to obtain a blank solution. The fluorescent probe solution for determining the crystallinity of hydrotalcite colloidal sol by fluorescence regulation based on π-π stacking and water are respectively mixed with hydrotalcite colloidal sols containing transition metals of different crystallinity and the same layer metal element composition to obtain mixed solutions. The concentrations of the fluorescent probe in the blank solution and the mixed solution are the same, and the concentrations of hydrotalcite in each mixed solution are the same. The blank solution and each mixed solution after the same reaction time are subjected to fluorescence detection, with an excitation wavelength of 340-342 nm and a detection wavelength of 450-470 nm. The difference in fluorescence intensity between the blank solution and the mixed solution is the fluorescence quenching value. A standard curve is prepared with the crystallinity as the horizontal axis and the fluorescence quenching value as the vertical axis. (2) The transition metal-containing hydrotalcite colloidal sol with the same layer metal element composition to be tested is prepared under the same preparation conditions to obtain a test mixed solution with the same fluorescent probe concentration and the same hydrotalcite concentration. After the reaction time is the same, fluorescence detection is performed under the same conditions, and the fluorescence quenching value is calculated. Then, the crystallinity is calculated based on the standard curve.
[0007] The solvent of the fluorescent probe solution is DMSO and / or ethanol.
[0008] The concentration of the fluorescent probe in the mixed solution is 10-20 μM, and the concentration of the hydrotalcite is 8-15 μg / mL.
[0009] The reaction time is at least 1 hour.
[0010] The present invention uses an imidazole-anchored naphthalene diamine (IANA) fluorophore with a planar naphthalene motif as a fluorescent probe. The imidazole group has a strong binding ability to transition divalent metal ions. After the transition metal is coordinated with imidazole, the ordered arrangement of IANA is enhanced, which is beneficial to the face-to-face π-π stacking of the planar naphthalene motif and inhibits the absorption of ultraviolet light, thereby causing fluorescence quenching. However, the internal structural orderliness and spatial atomic arrangement of materials with different crystallinity are different, which will lead to differences in the orderliness of the arrangement of IANA, affecting the quenching degree of the probe, and then the crystallinity can be measured by the quenching degree. The present invention uses π-π stacking to regulate fluorescence to measure the crystallinity of hydrotalcite colloidal sol, opening up a new way to explore alternatives to X-ray diffraction. BRIEF DESCRIPTION OF THE DRAWINGS
[0011] Figure 1 Characterization of the fluorescent probe (IANA). (a) Synthesis steps of IANA, (b) ESI-MS spectrum of IANA, (c) 1H NMR spectrum, (d) FT-IR spectrum of IANA, (e) fluorescence excitation (black line), emission (dashed line), and UV-visible absorption (gray line) spectra of IANA (20 μM); the inset shows the photos of IANA under visible light (left) and 365 nm UV light (right).
[0012] Figure 2 Characterization of CdAl-LDHs. XRD patterns (a), FT-IR spectra (b), TEM (c), and hydrodynamic diameter distributions (d) of CdAl-LDH-1, CdAl-LDH-2, CdAl-LDH-3, and CdAl-LDH-4.
[0013] Figure 3 Fluorescence emission spectra of IANA in the presence of different concentrations of CdAl-LDHs.
[0014] Figure 4 (a) Fluorescence emission spectra of IANA with and without the addition of CdAl-LDHs with different crystallinity, (b) time-dependent relative fluorescence intensity of IANA with the addition of CdAl-LDHs with different crystallinity.
[0015] Figure 5 Time-dependent fluorescence emission spectra of IANA in the presence of CdAl-LDH-1 (a), CdAl-LDH-2 (b), CdAl-LDH-3 (c), and CdAl-LDH-4 (d), respectively.
[0016] Figure 6 Time-dependent fluorescence emission spectra of IANA in the presence of CdAl-LDH-X.
[0017] Figure 7 Fluorescence emission spectra (a) and UV-visible absorption spectra (b) of IANA without (black line) and with (dashed line) CdAl-LDH-X, (c) standard curve of fluorescence quenching degree and crystallinity, (d) XRD pattern of CdAl-LDH-X.
[0018] Figure 8 XRD patterns of ZnAl-LDH-52.7%, ZnAl-LDH-61.1%, ZnAl-LDH-69.3% and ZnAl-LDH-79.9%.
[0019] Fig. 9 Time-dependent fluorescence emission spectra of IANA in the presence of ZnAl-LDH-52.7% (a), ZnAl-LDH-61.1% (b), ZnAl-LDH-69.3% (c), and ZnAl-LDH-79.9% (d), respectively.
[0020] Fig.10 Standard curve of fluorescence quenching degree and crystallinity of ZnAl-LDHs.
[0021] Fig.11 Fluorescence emission spectra of the supernatant after the reaction of IANA with CdAl-LDHs (dashed line) and ZnAl-LDHs (gray line).
[0022] Fig.12 Standard curve of fluorescence quenching degree and crystallinity of Cd2Al-LDHs.
[0023] Fig.13 Standard curve of fluorescence quenching degree and crystallinity of ZnCd2Al-LDHs.
[0024] Fig.14 XRD pattern of colloidal sol CdAl-LDHs.
[0025] Fig.15 Crystallinity values were calculated using fluorescence (black) and XRD (grey) methods. DETAILED DESCRIPTION
[0026] Example 1 Synthesis steps of the fluorescent probe (naphthalene diamine derivative fluorescent probe IANA) for determining the crystallinity of hydrotalcite colloidal sol based on π-π stacking regulation fluorescence: 2,3-diaminonaphthalene (0.15 g, 0.95 mmol) and imidazole-2-carboxaldehyde (0.10 g, 1.1 mmol) were dissolved in a mixed methanol-ethanol solvent (20 mL, v / v=1:1). The reaction was stirred under reflux for 24 hours. Then, the solution was cooled to room temperature, filtered, washed with methanol, and vacuum dried at 60°C for 12 hours to remove the residual solvent to obtain the product IANA (yellow solid) with a yield of 52%. IANA was dissolved in DMSO to prepare a fluorescent probe solution with a concentration of 1 mM for standby use.
[0027] The structural formula of the fluorescent probe prepared above is as follows: .
[0028] Example 2
[0029] Synthesis steps of CdAl-LDHs with different crystallinity: Solution A was prepared by dissolving 0.39 g Al(NO3)3·9H2O in 100 mL deionized water, and salt solution B was prepared by dissolving 0.82 g Cd(NO3)2·4H2O in 60 mL deionized water. The pH value of solution A was adjusted to 10.3 with saturated Ca(OH)2 solution. Under strong stirring, saturated Ca(OH)2 solution and solution B were slowly added to the reaction system at the same time to keep the pH value of the solution constant. The reaction was completed within 40 minutes, and the white precipitate was aged at 120°C for 10 h to obtain hydrotalcite, which was recorded as CdAl-LDH-4. The obtained hydrotalcite was divided into two equal volumes, recorded as sample 1 and sample 2, centrifuged at 10000 rpm in a centrifuge and washed with ethanol. Sample 1 was dried in an oven at 60°C and weighed; the weight of the hydrotalcite in sample 2 was the same as that of the hydrotalcite in sample 1. Using the weight of sample 1 as a control, the undried sample 2 was ultrasonically dispersed with water to obtain a colloidal sol with a concentration of 1 mg / mL for later use.
[0030] The above reaction time was adjusted to 5 min, pH 10.0, no aging, and other conditions were the same, and the obtained hydrotalcite was recorded as CdAl-LDH-1. The post-treatment method was the same to obtain a 1 mg / mL colloidal sol.
[0031] The above reaction time was adjusted to 10 min, pH 10.3, no aging, and other conditions were the same, and the obtained hydrotalcite was recorded as CdAl-LDH-2. The post-treatment method was the same to obtain a 1 mg / mL colloidal sol.
[0032] The above reaction time was adjusted to 40 min, pH 10.3, no aging, and other conditions were the same, and the obtained hydrotalcite was recorded as CdAl-LDH-3. The post-treatment method was the same to obtain a 1 mg / mL colloidal sol.
[0033] The above reaction time was adjusted to 10 min, pH 10.3, aging temperature 120°C, aging time 10 h, and other conditions were the same, and the obtained hydrotalcite was recorded as CdAl-LDH-X. The post-treatment method was the same to obtain a 1 mg / mL colloidal sol.
[0034] Application Example 1 Study on the fluorescence response of IANA and different concentrations of CdAl-LDHs-1: 0, 5, 10, 15, 20, 35 and 50 μL of CdAl-LDHs-1 colloidal sol were added to water to make the total volume 980 μL, mixed evenly, and then 20 μL of the IANA solution of Example 1 was added. After continuous shaking at 950 rpm for 1 hour at room temperature, the test was performed. The test scanning range was 360nm-600nm, the slit was 5nm, and the voltage was 600V. Figure 3As shown in the figure, under the excitation wavelength of 340 nm, as the LDHs content increased, the fluorescence peak at the wavelength of 462 nm was gradually quenched to almost disappear, proving that the fluorescence quenching degree of the IANA probe was related to the LDHs concentration and increased with the increase of concentration.
[0035] Application Example 2 Fluorescence response kinetics of the interaction between IANA and CdAl-LDHs with different crystallinity: Mix 20 μL of IANA solution with 980 μL of water to obtain a blank solution; add 15 μL of CdAl-LDHs-1 colloidal sol, CdAl-LDHs-2 colloidal sol, CdAl-LDHs-3 colloidal sol, and CdAl-LDHs-4 colloidal sol to 965 μL of water, mix well, and then add 20 μL of IANA solution to obtain a mixed solution, react at room temperature in an oscillator at 950 rpm and perform fluorescence kinetics test. Set the excitation wavelength to 340 nm, the test scanning range to 360 nm-600 nm, the slit to 5 nm, and the voltage to 600 V. Figure 4 As shown in Figure 1, the addition of CdAl-LDHs to IANA did not result in a visible change in the emission spectrum of IANA, despite significant fluorescence quenching. At the same time, the quenching efficiency is proportional to the crystallinity of CdAl-LDHs. Figure 4 As shown in (b), after adding CdAl-LDHs, the fluorescence intensity of IANA decreased rapidly. After 60 min of reaction, the fluorescence quenching degree of IANA reached >39%. These results indicate that the interaction between CdAl-LDHs and IANA may affect the fluorescence behavior of IANA. The fluorescence response kinetics of IANA to four CdAl-LDHs are shown in Figure 5 As shown, with the increase of the crystallinity of CdAl-LDHs, the internal structure order and spatial atomic arrangement become more regular, resulting in a more ordered arrangement of IANA after Cd-imidazole coordination, a stronger face-to-face π-π stacking, and differences in the degree of fluorescence quenching due to different crystallinity.
[0036] According to the fluorescence kinetic test spectrum obtained above, the fluorescence intensity values of the blank solution and each mixed solution (at 60 min reaction time) at 462 nm were extracted. The difference between the fluorescence intensity of the blank solution and the mixed solution was the fluorescence quenching value. The standard curve y=0.595x+21.135 was obtained with crystallinity as the abscissa and fluorescence quenching value as the ordinate. 2 =0.994, e.g. Figure 7 As shown in c.
[0037] Application Example 3 The CdAl-LDHs-X colloidal sol was prepared under the same conditions as in Application Example 2 to obtain a mixed solution to be tested, and fluorescence detection was performed. Figure 6 As shown in Figure 2, after adding CdAl-LDH-X, the fluorescence intensity of the IANA solution gradually decreased. By calculation, it was found that the degree of fluorescence quenching was close to 44.6% ( Figure 7 a). After adding CdAl-LDH-X, the UV-visible absorption spectrum of IANA also showed a significant decrease ( Figure 7 b). The fluorescence quenching value was calculated by the same method, and then the crystallinity was calculated to be 39.5% based on the standard curve. In order to verify the measurement accuracy, the XRD pattern of CdAl-LDH-X ( Figure 7 d) The calculated crystallinity of CdAl-LDH-X is 38.9%, which is close to the result of the fluorescence method mentioned above, with a relative error of 1.5%, indicating that the crystal detection method of the present invention has high accuracy.
[0038] Application Example 4 ZnAl-LDHs with different crystallinity were prepared into 1 mg / mL colloidal sol. Figure 8 As shown, the crystallinity calculated by XRD method is 52.7%, 61.1%, 69.3% and 79.9%, respectively. 30 μL of ZnAl-LDHs colloidal sols with different crystallinity were added to 950 μL of water, mixed evenly, and then 20 μL of IANA solution was added. The reaction was carried out at room temperature in an oscillator at a speed of 950 rpm and fluorescence kinetics test was performed. The test scanning range was 360nm-600nm, the slit was 5nm, and the voltage was 600V. Similar to CdAl-LDHs, after adding ZnAl-LDHs, the fluorescence intensity of IANA decreased rapidly ( Fig. 9 ).at the same time, Fig.10 It shows that there is a good linear relationship between the fluorescence quenching degree of IANA and the crystallinity of ZnAl-LDHs at 60 min (y=0.611x+0.450, R 2 =0.998). The fluorescence quenching degree of ZnAl-LDHs is lower than that of CdAl-LDHs, which indicates that there may be different quenching efficiencies. Fig.11 As shown, 15 μL ZnAl-LDHs and CdAl-LDHs were added to 965 μL water respectively, mixed evenly, and then 20 μL IANA solution was added. The reaction was carried out for 60 min. The fluorescence intensity of the supernatant was tested and showed obvious differences, indicating that compared with ZnAl-LDHs, CdAl-LDHs had a stronger binding ability to IANA.
[0039] Application Example 5 Cd2Al-LDHs (Cd / Al=2 / 1) and ZnCd2Al-LDHs with different crystallinity were prepared under the same preparation and detection conditions as in Application Example 2. The crystallinity calculated by XRD method was fitted with the fluorescence quenching degree of IANA at 60 min of reaction. The results showed that there was a good linear relationship between the fluorescence quenching degree of IANA and the crystallinity of Cd2Al-LDHs and ZnCd2Al-LDHs. The fitting standard curves were y=0.485x+18.178, R 2 =0.996; y=0.615x+16.634, R 2 =0.997; Fig.12 and Fig.13 shown.
[0040] Application Example 6 Application of fluorescence technology to detect the crystallinity of layered materials in actual synthesis and testing: Based on Example 2, five CdAl-LDHs with different crystallinity were synthesized by changing the reaction pH and temperature. Fig.14 ), and a series of tests were conducted. The fluorescence quenching degree of CdAl-LDHs with different crystallinity was obtained through fluorescence quenching kinetics. According to the linear relationship (Application Example 2), the crystallinity of the five CdAl-LDHs was calculated to be 36.0%, 44.2%, 51.8%, 61.4% and 70.0%, respectively. The corresponding crystallinity calculated by XRD technology was 34.9%, 43.0%, 50.9%, 60.3% and 68.7%, respectively ( Fig.15 ). The crystallinity of different methods is very close.
Claims
1. A fluorescent probe for measuring the crystallinity of hydrotalcite colloidal sol based on π-π stacking-regulated fluorescence, characterized in that: The structural formula of the fluorescent probe shown is as follows: 。 2. A method for preparing a fluorescent probe for determining the crystallinity of hydrotalcite colloidal sol based on π-π stacking-regulated fluorescence, characterized in that: The specific operation of the preparation method is: dissolving 2,3-diaminonaphthalene and imidazole-2-carboxaldehyde in a methanol-ethanol mixed solvent with a volume ratio of 0.5-2, heating under reflux for 20-30 hours, cooling to room temperature, filtering, washing with methanol, and drying at 60-80° C. to obtain the fluorescent probe.
3. A method for determining the crystallinity of hydrotalcite colloidal sol, characterized in that: The specific steps of the method are: (1) A fluorescent probe solution for determining the crystallinity of hydrotalcite colloidal sol by fluorescence regulation based on π-π stacking is mixed with water to obtain a blank solution. The fluorescent probe solution for determining the crystallinity of hydrotalcite colloidal sol by fluorescence regulation based on π-π stacking and water are respectively mixed with hydrotalcite colloidal sols containing transition metals of different crystallinity and the same layer metal element composition to obtain mixed solutions. The concentrations of the fluorescent probe in the blank solution and the mixed solution are the same, and the concentrations of hydrotalcite in each mixed solution are the same. The blank solution and each mixed solution after the same reaction time are subjected to fluorescence detection, with an excitation wavelength of 340-342 nm and a detection wavelength of 450-470 nm. The difference in fluorescence intensity between the blank solution and the mixed solution is the fluorescence quenching value. A standard curve is prepared with the crystallinity as the horizontal axis and the fluorescence quenching value as the vertical axis. (2) The transition metal-containing hydrotalcite colloidal sol with the same layer metal element composition to be tested is prepared under the same preparation conditions to obtain a test mixed solution with the same fluorescent probe concentration and the same hydrotalcite concentration. After the reaction time is the same, fluorescence detection is performed under the same conditions, and the fluorescence quenching value is calculated. Then, the crystallinity is calculated based on the standard curve.
4. The method according to claim 3, characterized in that The solvent of the fluorescent probe solution is DMSO and / or ethanol.
5. The method according to claim 3, characterized in that: The concentration of the fluorescent probe in the mixed solution is 10-20 μM, and the concentration of the hydrotalcite is 8-15 μg / mL.
6. The method according to claim 3, characterized in that The reaction time is at least 1 hour.
Citation Information
Patent Citations
CeF3-based up-conversion luminescent material as well as preparation method and application thereof
CN113088277A
Naphthalene diamine derivative fluorescent probe and application thereof in monitoring isomorphic substitution process of heavy metal
CN116589412A
Benzocarbazole-intercalated layered double hydroxides composite luminescent material and its preparation method
US20100130750A1
Cited By
Naphthalene diamine derivative fluorescent probe and application thereof in monitoring isomorphic substitution process of heavy metal
CN116589412A